Ovarian masses in pediatric patients: a multicenter study of 98 surgical cases in Tunisia. (4th March 2018) - Abid, I.; Zouari, M.; Jallouli, M.; Sahli, S.; Bouden, A.; Ben Abdallah, R.; Trabelsi, F.; Jabloun, A.; Charieg, A.; Mrad, C.; Marzouki, M.; Mosbahi, S.; et al.
Abstract: Ovarian masses requiring surgical intervention are uncommon in the pediatric population. Our aim is to report results of a multicentric Tunisian study concerning the clinical practice and the management of pediatric ovarian masses and to identify the factors that are associated with ovarian preservation. Between January 2000 and December 2015, 98 pediatric patients (<14 years) were surgically treated for ovarian masses at the five pediatric surgery departments in Tunisia. Ninety-eight patients were included in this study. The mean age of the patients at time of surgery was 8.46 ± 4.87 years. Sixty-three ovarian masses (64.3%) were non-neoplastic lesions, 24 (24.5%) were benign tumors, and 11 (11.2%) were malignant neoplasms. Conservative surgery (ovarian-preserving surgery) was successfully performed in 72.4% of the benign lesions, whereas only three patients (27.3%) with malignant tumors underwent ovary-sparing tumor resection ( p  < .001). The mean diameter of the tumors in the patients who underwent oophorectomy was significantly larger than that in the patients who underwent conservative surgery (7.8 ± 3.9 cm vs. 5.7 ± 2.9 cm, respectively, p  = .001). In our study, the risk factors for oophorectomy were a malignant pathology and large tumor size. In accordance with the Gynecologic Cancer Intergroup consensus, we recommend that surgical management of ovarian masses in children should be based on ovarian-preserving surgery.